Figuring the Past Period Film and the Mannerist aesthetic - Vidal, Belén (Film Culture in Transition, 2012)
This definitive work offers a new approach to the period film at the turn of the twenty-first century, examining the ways in which contemporary cinema recreates the historical past. This book explores the relation between visual motifs and cultural representation in a range of key films by James Ivory, Martin Scorsese and Jane Campion, among others. Looking at the mannerist taste for citation, detail and stylisation, the author argues for an aesthetic of fragments and figures central to the period film as an international genre. Three key figures - the house, the tableau and the letter - structure a critical journey through a selection of detailed case studies, in relation to changing notions of visual style, melodrama, and gender. This seeks to place this popular but often undervalued genre in a new light and to rethink its significance in the context of key debates in film studies.